Iglesia de Cristo/Iglesia Católica. Acercamiento Histórico-Sistemático a la Interpretación Católica de la Fórmula «Subsistit In» (2021)
It is indisputable that the Vatican II meant an important change of paradigm of huge dimension for the Catholic Church concerning the interconfesional dialogue and the underlying ecclesiology to its ecumenical proposal. The Dogmatic Constitution Lumen Gentium (LG) is one of the central documents of the Vatican II and it was thought as a first step for a new age of the Church’s self understanding. Is in this sense that we will analyze the highly disputed and controversial declaration «subsistit in» from LG 8 as a replacement of the Vatican I «est», as long as its dogmatical, eclesial and pastoral implications.